UNCOVERING THE RESILIENCE AND STRESS FACTORS OF EFL TEACHERS: A NARRATIVE STUDY - Syabilla, Zalsa Febrina; Ubaidillah, M. Faruq; Mustofa, Mutmainnah; Romadhon, M. Galuh Elga (University of Kuningan, 2024)
EFL teachers typically confront an abundance of problems that can lead to stress and have an influence on their resilience. Understanding resilience and stress can help improve well-being and education. This qualitative study tried to figure out the resilience and stress factors faced by EFL teachers across educational levels. The narrative inquiry involved an in-depth semi-structured interview administered to four EFL teachers across primary, middle, and secondary levels. The findings indicate that EFL teachers across educational levels encounter similar stressors, such as heavy workloads, student behavior, and low salary. Surprisingly, there were differences in stress factors and resilience strategies utilized by teachers across educational levels. The primary-level teacher reported more stress when dealing with students’ behavior, whereas middle-level teacher was stressed by students’ behavior and resources, and high school teacher by resource constraints and encouraged student engagement. Regarding resilience strategies, teachers at all levels indicated seeking support from family and friends but also using different coping methods such as meditation, leisure activities, and positive thinking. The findings suggest the importance of understanding the unique stress factors faced by EFL teachers across educational levels and establishing targeted support programs to enhance teacher resilience.